Rate and predictors of 30-day readmission for clostridiodes difficile: a United States analysis. (31st December 2022) - Kichloo, Asim; El-amir, Zain; Dahiya, Dushyant Singh; Al-Haddad, Mohammad; Singh, Jagmeet; Singh, Gurdeep; Corpuz, Carlos; Shaka, Hafeez
Abstract: Background: Clostridiodes difficile is a leading cause of healthcare-associated diarrhea. In this study, we aimed to identify the rates and predictors for 30-day readmissions of Clostridiodes difficile Enterocolitis (CDE) in the United States. Methods: We conducted a retrospective study of the Nationwide Readmissions Database to identify adult hospitalizations with a principal diagnosis of CDE for 2018. Individuals <18 years old and elective hospitalizations were excluded. Primary outcomes included readmission rate and the top ten principal diagnosis on readmission, while the secondary outcomes were inpatient mortality, hospital costs and independent predictors of 30-day all-cause readmissions. Furthermore, we devised a scoring system to estimate the risk of CDE readmissions. Stata® Version 16 was used for statistical analysis and p -values ≤0.05 were statistically significant. Results: We identified 94, 668 index hospitalizations and 18, 296 readmissions at 30-days for CDE in 2018. The 30-day all-cause readmission rate was 25.7%. On readmission, CDE was the most common principal diagnosis (25.7%), followed by unspecified sepsis, and acute renal failure. A female predominance was also noted for index and 30-day readmissions of CDE. Compared to index admissions, we noted higher odds of inpatient mortality [4.4 vs 1.4%, Odds Ratio (OR):3.32, 95% Confidence Interval (CI):2.87–3.84, p  < 0.001], longer mean length of stay (LOS) [6.4 vs 5.6 days, Mean Difference (MD):0.9, 95% CI:0.7–1.0, p  < 0.001), and higher mean total hospital charge (THC) [$56, 015 vs $40, 871, MD:15, 144, 95% CI:13, 260–17, 027, p  < 0.001] for 30-day readmissions of CDE. Independent predictors for 30-day all-cause readmissions of CDE included discharged against medical advice (AMA) [Adjusd Hazard Ratio (aHR):2.01, 95% CI:1.73–2.53, p  < 0.001], diabetes mellitus (DM) [aHR:1.22, 95% CI:1.16–1.29, p  < 0.001], and chronic kidney disease (CKD) [aHR:1.29, 95% CI:1.21–1.37, p  < 0.001]. Conclusion: The all-cause 30-day readmission rate and inpatient mortality for CDE was 25.7% and 4.4%, respectively. Discharge AMA, DM and CKD were independent predictors for 30-day all-cause readmissions of CDE. KEY MESSAGE: The 30-day all-cause readmission rate for Clostridiodes difficile Enterocolitis was noted to be 21.4% in 2018. Independent predictors of 30-day all-cause readmissions for Clostridiodes difficile Enterocolitis include diabetes mellitus, discharged against medical advice and chronic kidney disease. Readmissions of Clostridiodes difficile Enterocolitis had higher mortality rates, healthcare cost and length of hospital stay compared to index admissions.